THE ROLE OF TEACHERS AND STUDENTS IN DEALING WITH EDUCATION IN THE PANDEMIC TIME OF COVID-19: PERAN GURU DAN MAHASISWA DALAM MENGHADAPI PENDIDIKAN PADA WAKTU PANDEMI COVID-19 - Herrie Kurniawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
purpose of writing this article is to discuss the role of teachers and students in facing education during the Covid-19 pandemic. This writing method uses descriptive analysis method by reviewing the education system that occurred during the Covid-19 pandemic and seeing the role between teachers and students in facing the world of education during the Covid-19 pandemic. This descriptive analysis method will be collected and some reinforcing data will be provided for educational problems during the Covid-19 pandemic. The results of this writing will be useful in seeing how effective the education and learning system is for teachers and students in facing the Covid-19 pandemic and also whether education in Indonesia is ready to face the new learning system, especially for teachers and students who are facing online learning. during the Covid-19 pandemic.